ENTREPRENEURIAL MOTIVATION AMONG ECONOMICS AND MANAGEMENT STUDENTS: THE ROLE OF ENTREPRENEURSHIP EDUCATION - Haq, Muhamad Bai’ul; Septiawan, Adi; Suhardi, Rizal M. (Universitas Islam Negeri Mataram, 2022)
The government's biggest concerns are multifaceted unemployment and poverty. Unemployment and poverty are inextricably linked to social, cultural, and political challenges, as well as educational quality. Young people are one of the most important contributors. This phenomenon is a significant challenge for various stakeholders. Efforts are being made to encourage the entrepreneurial spirit, significantly changing the mindset of young people and job seekers. The role of education must be adequately maximized through the transformation of the student learning curriculum system. Entrepreneurship education is crucial to explain the variables of student motivation in developing an entrepreneurial spirit. Therefore, researchers are committed to analyzing how the role of entrepreneurship education implemented at the Faculty of Economics and Business, Mataram University (FEB UNRAM) campus, especially for economics and management students. This study uses a type of quantitative research. Researchers use a questionnaire given to the research sample respondents for the data collection technique. The data analysis method used is the linear regression analysis method using the IBM SPSS Statistics software. The results of the study indicate that there is a significant influence between entrepreneurship education on students' entrepreneurial motivation. The calculated results show this (3.291) > stable (1.65), then the t coefficient is significant so that Ha is accepted.